Evidence of dipstick superiority over urine microscopy analysis for detection of hematuria. (December 2016) - Bataille, Aurélien; Wetzstein, Morgane; Hertig, Alexandre; Vimont, Sophie; Rondeau, Eric; Galichon, Pierre
Abstract Background There is an unresolved debate on the best screening method for hematuria as a symptom of glomerulonephritis or urological malignancies. The urinary dipstick is generally considered as an imperfect surrogate for urine microscopy analysis. Results We designed a study to compare urine microscopy analysis, urinary dipstick and flow cytometry, using controlled dilutions of blood in urine samples from volunteers collected in two different physiologically-relevant conditions (basal state and hyperhydration). We found that although all techniques were 100 % effective in detecting hematuria at basal state, these results were variably reproduced when testing the same final amount of hematuria in urine collected after hyperhydration. Our data shows a variable sensitivity for the detection of hematuria by urine microscopy analysis or flow cytometry, but not by urinary dipstick. Conclusions Urinary dipstick qualifies as a better screening test for hematuria than urine microscopy analysis or flow cytometry, as it is sensitive and performs better in unstandardized conditions. It is universally available and also faster and cheaper than cytometric techniques.